Body-Surface-Potential-Mapping - Konrad, Torsten; Theis, Cathrin; Mollnau, Hanke; Sonnenschein, Sebastian; Rostock, Thomas (Kardiologie up2date, 2014)
Persistent atrial fibrillation is a common heart rhythm disturbance and a leading cause of hospitalization and death. Current available therapy remains suboptimal. Catheter ablation of responsible cardiac tissue is more effective than medications, but a substantial proportion of patients require repeat procedures. Also the optimal ablation strategy remains unclear. Organized re-entrant circuits (rotors) and focal impulses may sustain persistent atrial fibrillation. Body-Surface-Mapping techniques are available from the medical companies Amycard and CardioInsight. These systems can analyse the atrial fibrillation activity from the body surface and localize it with a high spatial resolution (with up to 252 electrodes covering the thorax). These systems are under investigation for ablation of persistent atrial fibrillation.